My five senses - Aliki (New York : HarperCollins, 1989)
Relates the excitement a child feels when discovering the world through the use of the five senses.
Book Links (A.L.A.).
Elem. School Library Collection.
Wilson's Children.
1.7
K-3
Keywords: Senses and sensation -- Juvenile Literature; Senses and sensation; Senses and sensation